1999
DOI: 10.1038/sj.bjc.6690427
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of loss of heterozygosity at loci on chromosome 17p13.3-ter in sporadic breast cancer is evidence for a putative tumour suppressor gene

Abstract: Summary Several studies indicate that the short arm of chromosome 17 is one of the most frequently altered regions in sporadic breast carcinomas (45-60%). In the present report the 17p13.3-ter locus in tumour DNA of breast cancer patients, along with their matching normal lymphocyte DNA, have been mapped with four markers (D17S5, D17S379, ABR and D17S34), spanning nearly 3 cM of the telomer. Sixty-five of 143 heterozygous tumours had lost at least one of the markers at the minimum region of loss (45%). High le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
(24 reference statements)
2
16
1
Order By: Relevance
“…In the present study we have also shown that HIC-1 expression (seven cancers) was associated with YNZ22 LOH (P = 0.015, two-tailed Fisher's exact test) a result which concurs with that previously reported (Fujii et al, 1998). Given the link between YNZ22 LOH and poor prognosis in breast cancer Liscia et al, 1999) one might expect HIC-1 expression would correlate with poor prognosis. These differing associations suggest that HIC-1 may be distinct from a second gene involved in breast cancer marked by YNZ22.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study we have also shown that HIC-1 expression (seven cancers) was associated with YNZ22 LOH (P = 0.015, two-tailed Fisher's exact test) a result which concurs with that previously reported (Fujii et al, 1998). Given the link between YNZ22 LOH and poor prognosis in breast cancer Liscia et al, 1999) one might expect HIC-1 expression would correlate with poor prognosis. These differing associations suggest that HIC-1 may be distinct from a second gene involved in breast cancer marked by YNZ22.…”
Section: Discussionsupporting
confidence: 92%
“…More detailed studies of allelic imbalance in breast cancer, using markers spanning 17p13.3 has further refined the deletion map (Stack et al, 1995). Furthermore, LOH at YNZ22 can occur in the absence of p53 mutation, deletion or over-expression (Cornelis et al, 1994;Thompson et al, 1998) suggesting both regions may be of clinical importance in sporadic breast cancer Liscia et al, 1999). In addition, supportive evidence for the involvement of a tumour suppressor gene, distinct from p53 on chromosome 17p, is strengthened by the functional suppression of malignancy observed following the transfection of chromosome 17 (but not with chromosome 13) into breast cancer cell lines by micro cellmediated chromosome transfer and analysis of the resulting deletions (Casey et al, 1993;Theile et al, 1995).…”
mentioning
confidence: 99%
“…The presence of VNTR1 LOH without TP53 mutations could suggest that the tumor is still in an early stage. On the other hand, some tumors may display a TP53 mutation without LOH at 17p13 as observed in breast cancer (28,39,40), hepatocellular carcinoma (28), oral squamous cell carcinoma (30), and gastric cancer (38). In our series, the study of mRNA in four of seven mutated tumors without VNTR1 LOH showed that, in three of four, only the mutated allele is present.…”
Section: Discussionmentioning
confidence: 82%
“…In several studies, this deletion region was not accompanied by loss of heterozygosity (LOH) at the linked p53 locus located at 17p13.1, suggesting the presence of an additional tumor suppressor gene(s) located in 17p13.3 (Saxena et al 1992;Phillips et al 1993Phillips et al , 1996aCornelis et al 1994;Merlo et al 1994;Schultz et al 1996;Chattopadhyay et al 1997;Liscia et al 1999;Hoff et al 2001). Interestingly, allelic loss at D17S28 and D17S5 also occurs in many other types of cancer, including breast, lung, and brain malignancies (Saxena et al 1992;Merlo et al 1994;Konishi et al 1998;Phelan et al 1998;Liscia et al 1999;Hoff et al 2001).…”
mentioning
confidence: 99%